SEBERAPA PENTING MAQASHID AL-SYARI'AH DI ERAKONTEMPORER - Fithri, Naylal (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2021)
This study aims to find out the importance of Maqashid al-Syari'ah JaseerAuda's thinking in the field of Islamic law and how Islamic law is facingthe contemporary era. Using Qualitative Research Methods with LibraryResearch approach. The results showed that in conducting studies ofIslamic law should be able to distinguish between sharia and fiqh areas.Because a person's understanding of religion in the form of jurisprudationis strongly influenced by sociological, economic and political factors of hissociety. So that the presence of Islamic law cannot be separated from thepurpose and purpose of the application of Islamic sharia in order to createa benefit in the hereafter and the world by rejecting mudharat.